Relationships between inappropriate eating habits and problematic alcohol use, cigarette and waterpipe dependence among male adolescents in Lebanon - Jana Berro; Marwan Akel; Souheil Hallit; Sahar Obeid (BMC, 2021)
Abstract Background it is important to investigate the relationship between disordered eating in male adolescents and smoking and alcohol consumption as they are risk factors to other diseases as well. For example, high levels of alcohol accompanied by the acidic damage and nutritional deficit exhibited in people with disordered eating habits - due to induced vomiting - has been shown to increase risk of esophageal cancer. Considering the very few studies done on disordered eating prevailing in males and the prevalence of smoking and drinking habits, our study aims to investigate the correlation between inappropriate eating habits and one's dependence on cigarettes, waterpipes, and alcohol all the while focusing on male adolescents. Methods This was a cross-sectional observational study that enrolled 389 male students (13-17 years of age) drawn from five Lebanese schools between October and December 2019. Results The MANCOVA analysis was performed taking the addiction scales as the dependent variables and the EAT-26 score as an independent variable, adjusting for the covariates (age, BMI and household crowding index). Higher EAT-26 scores (more inappropriate eating attitudes) were significantly associated with higher waterpipe dependence (B = 0.11; CI 0.06-0.17) and more problematic alcohol use (B = 0.08; CI 0.04-0.12), but not cigarette dependence. Conclusions This study revealed an association between inappropriate eating and increased drinking and smoking the waterpipe, but not cigarettes. The manifestation of inappropriate eating habits was found to be significant among male adolescents; in the literature, this is also true for female adolescents. In Lebanon, the engagement of adolescents in alcohol drinking and waterpipe smoking is frequent as they are accessible due to the lack of law enforcement and supervision in the country. In addition, while this study found an association between inappropriate eating habits and dependency on smoking and drinking, further investigation should be done on the role of one's psychology in their exhibition of disordered eating as means to prevent the manifestation of these habits.